Biobased dual-cure thiol-ene benzoxazine resins for high-performance polymer dielectrics - Lu, Yong (2023)
In the present study, two magnolol based main chain benzoxazine polymers (MCBPs) are designed, synthesized and formulated into thiol-ene resins to develop high-performance polymer dielectrics. Initially, the thiol-ene thermoset films, Mag-M-4SH-80 and Mag-E-4SH-80, are obtained respectively using click chemistry. Being post cured via progressive temperature stage, Mag-M/E-4SH-80 performs complete ring opening polymerization and forms dual-cure polybenzoxazine (PBZ) products with excellent thermal and mechanical performances such as a high Tg of 236 °C and a flexure modulus of 2.5 GPa. Moreover, the thiol component of the resin introduces numerous dipoles to the resultant polymer networks, resulting in promising dielectric performances of the resin at both room temperature and elevated temperature. For instance, the Mag-M-4SH-80 film demonstrates a superior energy density (Ue) of 7.0 J/cm3@25 °C, which is among the top reported dielectric thermosets having same efficiency, and Mag-M-4SH-150 film reveals a Ue of 1.1 J/cm3@150 °C, significantly higher than the reported values of a great number of commercial heat resistant polymers. Herein, our findings not only expand the library of high-performance thiol-ene benzoxazine resins but also present their potentials as flexible dielectrics for energy storage for the first time, thus advance the functionality and capability of benzoxazine based materials in modern electronics.